Research on probe fault detection of EAST magnetic diagnostic system. (1st December 2022) - Li, Tingyu; Shen, Biao; Shi, Tonghui; Chen, Dalong; Guo, Bihao; Luo, Zhengping; Huang, Yao; Chen, Ming; Xiao, Bingjia
Abstract: The magnetic diagnostic system provides input signals for equilibrium reconstruction and plays a key role in plasma feedback control. Real-time monitoring and abnormal signal detection in the magnetic diagnostic system are of significance for the operation of a tokamak. In this paper, a general fault detection algorithm is proposed, based on the spatial autocorrelation of the probes. This algorithm first obtains a linear mapping between the expected value of each probe and the measured values of its adjacent probe combination through regression fitting, and then sets the fault detection threshold initially based on the fitting result of the absolute error distribution. In addition, the fault probe location is realized through a voting mechanism. The algorithm can simultaneously realize the fault detection of multiple non-adjacent probes. Based on the experimental data from the EAST, the method described here shows good performance and potential for use in long-pulsed operation.